2017
DOI: 10.1139/cjps-2016-0292
|View full text |Cite
|
Sign up to set email alerts
|

Benefit of tank-mixing dicamba with glyphosate applied post-emergence for weed control in dicamba plus glyphosate resistant soybean

Abstract: Soybean resistant to both glyphosate and dicamba (Roundup Ready 2 Xtend™) has been developed by Monsanto Inc. and was commercially available for the first time in Canada in 2017. Six field trials were conducted over a 2-yr period (2014-2015) at three locations in southwestern Ontario to determine whether there is a benefit of including dicamba in a postemergence application of glyphosate at two application timings for the control of non-glyphosate-resistant weeds in Roundup Ready 2 Xtend™ soybean. Adding dicam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…In contrast to percent control, glyphosate + dicamba applied alone POST provided greater Palmer amaranth biomass reduction of 97% compared to 76% reduction with glyphosate at 28 d after POST (Table 4). However, Underwood et al (2017) reported similar redroot pigweed biomass reduction of 90 to 94% with glyphosate applied alone or tank-mixed with dicamba. Pre-emergence herbicides followed by glyphosate + dicamba or glyphosate had similar biomass reduction of 76 to 98%, except acetochlor + clopyralid + flumetsulam applied (v/v).…”
Section: Monthmentioning
confidence: 89%
See 1 more Smart Citation
“…In contrast to percent control, glyphosate + dicamba applied alone POST provided greater Palmer amaranth biomass reduction of 97% compared to 76% reduction with glyphosate at 28 d after POST (Table 4). However, Underwood et al (2017) reported similar redroot pigweed biomass reduction of 90 to 94% with glyphosate applied alone or tank-mixed with dicamba. Pre-emergence herbicides followed by glyphosate + dicamba or glyphosate had similar biomass reduction of 76 to 98%, except acetochlor + clopyralid + flumetsulam applied (v/v).…”
Section: Monthmentioning
confidence: 89%
“…However, Crow et al (2016) reported greater (89%) control of >20-cm tall Palmer amaranth with glyphosate + dicamba compared to glyphosate (69%) at 28 d after POST. Underwood et al (2017) reported greater redroot pigweed (Amaranthus retroflexus L.) control of 99% with glyphosate + dicamba compared to 94% control with glyphosate at 14 d after POST. In contrast to percent control, glyphosate + dicamba applied alone POST provided greater Palmer amaranth biomass reduction of 97% compared to 76% reduction with glyphosate at 28 d after POST (Table 4).…”
Section: Monthmentioning
confidence: 99%
“…Dicamba is typically tank mixed with other components (e.g., water conditioner, other herbicides with different SOAs, drift reduction agent [DRA], adjuvant) to broaden the spectrum of weed control and improve performance (Anonymous 2019b;Anonymous 2019a;Roskamp et al 2013;Spaunhorst et al 2014). Glyphosate is a common tank-mix partner used to broaden the spectrum of weed control (e.g., grass species) (Underwood et al 2017). Glyphosate is a weak acid (Shaner et al 2014) that is formulated as various salts (e.g., isopropylamine, potassium) with low formulation pH.…”
Section: Introductionmentioning
confidence: 99%
“…Glyphosate is a WSSA Group 9 herbicide that has broad-spectrum activity on both monocots and dicots (Shaner et al 2014). Growers often prefer to apply glyphosate as a tank mixture with other herbicides, and the addition of glyphosate may help growers control other weed species against which dicamba alone would be weak (Underwood et al 2017). The MoA of glyphosate works by inhibiting the biosynthesis of aromatic amino acids through the EPSPS pathway (Amrhein et al 1980).…”
Section: Introductionmentioning
confidence: 99%
“…The focus of the study was on the time of application, within a 24-h period, using dicamba, glyphosate, and a mixture of both herbicides, and to determine the effect of weed height and TOD on herbicide efficacy. Although this study focuses on dicamba, glyphosate was included because it is affected by photoperiod differences (McAllister and Haderlie 1985), as well as being a common mixture with dicamba in the Georgia cotton-growing region (Underwood et al 2017). Experiments evaluated the influence on weed control of diurnal time of herbicide application of dicamba, glyphosate, and a combination of the two.…”
Section: Introductionmentioning
confidence: 99%